2020
DOI: 10.1530/ec-20-0472
|View full text |Cite
|
Sign up to set email alerts
|

Pheochromocytoma/paraganglioma preclinical models: which to use and why?

Abstract: Pheochromocytomas/paragangliomas (PPGLs) are rare neuroendocrine tumours linked to more than 15 susceptibility genes. PPGLs present with very different genotype/phenotype correlations. Certainly, depending on the mutated gene, and the activated intracellular signalling pathways, as well as their metastatic potential, each tumour is immensely different. One of the major challenges in in vitro research, whatever the study field, is to choose the best cellular model for that study. Unfortunately, most of the tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 57 publications
(67 reference statements)
0
9
0
Order By: Relevance
“…Pseudohypoxic PPGLs are more prone to develop metastatic disease [5], but available in vitro models often lack typical characteristics of a pseudohypoxic phenotype, such as an immature catecholamine phenotype, increased pro-metastatic behavior, and upregulation of hypoxia-related genes under normoxic conditions [11]. Based on the hypothesis that recurrent cycles of extrinsic hypoxia (≤1% oxygen) leads to a manifestation of a pseudohypoxic phenotype, we established PC12 sub-cell lines using repeated exposure to hypoxia-reoxygenation cycles.…”
Section: Recurrent Cycles Of Hypoxia Lead To the Establishment Of A P...mentioning
confidence: 99%
See 1 more Smart Citation
“…Pseudohypoxic PPGLs are more prone to develop metastatic disease [5], but available in vitro models often lack typical characteristics of a pseudohypoxic phenotype, such as an immature catecholamine phenotype, increased pro-metastatic behavior, and upregulation of hypoxia-related genes under normoxic conditions [11]. Based on the hypothesis that recurrent cycles of extrinsic hypoxia (≤1% oxygen) leads to a manifestation of a pseudohypoxic phenotype, we established PC12 sub-cell lines using repeated exposure to hypoxia-reoxygenation cycles.…”
Section: Recurrent Cycles Of Hypoxia Lead To the Establishment Of A P...mentioning
confidence: 99%
“…This provides a rational for targeting HIF2α and DNA methylation in metastatic PPGLs, particularly for those with mutations in SDHB. Currently available preclinical in vitro models to evaluate such novel therapeutic approaches present with different limitations and often lack characteristic features of aggressive cluster 1 PPGLs [11,12]. Moreover, genetically engineered cell lines only reflect the changes associated with the particular mutation and do not allow for general conclusions about the increased aggressiveness of cluster 1 tumors and the associated therapeutic response.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, they can be easily standardized, and yet, they provide enough complexity, such as 3D geometry, to represent relevant aspects of human tumours [ 38 ]. Spheroids generation facilitates the growth of highly uniform spheroids and allow real-time monitoring of drug-induced changes in their phenotypes [ 27 , 39 , 40 ]. We previously demonstrated that TME, represented by primary CAFs, plays a fundamental and specific role in inducing the invasion properties of spheroid cells and that this effect is extraordinarily enhanced in MTT SDHB sil ones [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…It will be of major interest for future studies to evaluate discrepancies between the models in more detail, also with respect to dysfunction of other SDH subunits. However, to date no comparable models with knockout of the different subunits is available (56).…”
Section: Discussionmentioning
confidence: 99%